Pengaruh Online Customer Review Dan Kualitas Informasi Terhadap Keputusan Pembelian Dengan E-Trust Sebagai Variabel Intervening Pada Fitur Shopee Live - Sudrajat, Putri Alviyana Dewi; Nurlenawati, Netti; Triadinda, Dexi (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research aims to find out how online customer reviews affect E-Trust, find out the effect of information quality on E-Trust, find out how E-Trust influences purchasing decisions, find out how online customer reviews influence purchasing decisions through E-Trust as an intervening variable, and find out the quality of information influences purchasing decisions via E-Trust as an intervening variable. This research method is quantitative by distributing questionnaires to 180 respondents via Google Form. In this research, researchers used path analysis with the help of the SmartPLS 3.0 application. The population in this research were 180 Shopee Live IKIACES customers. The results of the research obtained were the direct influence of online customer reviews on e-trust has a positive and significant effect, as well as the direct influence of information quality on e-trust has a positive and significants effect. The influences of e-trust on purchasing decisions also has a positive and significants effect. The research results for the e-trust variable intervening variable in this research are able to act as mediation so that it can strengthen the influence of online customer reviews (X1) and information quality (X2) which are independent variables on purchasing decisions as the dependent variable.